Interactions between muscle volume and body mass index on brain structure in the UK Biobank - Lu, Alicia; Than, Stephanie; Beare, Richard; La Hood, Alexandra; Collyer, Taya Annabelle; Srikanth, Velandai; Moran, Chris (Frontiers in Dementia, 2024)
Low skeletal muscle volume may increase dementia risk through mechanisms that also affect brain structure. However, it is unclear whether this relationship exists outside of sarcopenia and/or varies by other factors. We aimed to study the interplay between skeletal muscle volume and factors such as age, sex, and body mass index (BMI) in explaining brain structure at midlife in a cohort without sarcopenia.We used abdominal and brain magnetic resonance imaging (MRI) data from a population-based cohort of people enrolled in the UK Biobank. The following measures were derived: thigh fat-free muscle (FFMV), total brain volume (TBV), grey matter volume (GMV), white matter volume (WMV), total hippocampal volume (THV), and white matter hyperintensity volume (WMHV). Participants below sex-based grip strength thresholds suggesting probable sarcopenia were excluded. Linear regression analysis was used to study the interaction or mediation effects of age, sex, and BMI on the associations between FFMV and brain volumes.Data were available for 20,353 participants (median age 64 years, 53% female). We found interactions between thigh FFMV, BMI, and age (all p<0.05). Greater thigh FFMV was associated with better brain volumes in those aged less than 64 years with normal (TBV:β=2.